(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Uzbekistan’s rich historical and cultural heritage has the potential to attract visitors from different parts of the world. However, it is clear that there are challenges that need to be overcome in order to fully realize this potential. The article includes proposals for infrastructure development and service provision. Quality improvement and promotion efforts offer a strategic roadmap for the development of the country’s tourism industry. By investing in these areas and implementing supportive policies, Uzbekistan can become more competitive and can move towards becoming an attractive tourist center. With the right initiatives, the country will definitely achieve significant growth in the tourism sector..